Human Fungal Infections: Diagnostic and Therapeutic Challenges - Timoleon-Achilleas Vyzantiadis; Eleni Gavriilaki; Athanasios Tragiannidis (Journal of Fungi)
Fungal infections, either invasive and disseminated or cutaneous and superficial, are an important and increasing cause of morbidity [...]